New femoral remains of Nacholapithecus kerioi: Implications for intraspecific variation and Miocene hominoid evolution. Issue 155 (June 2021) - Pina, Marta; Kikuchi, Yasuhiro; Nakatsukasa, Masato; Nakano, Yoshihiko; Kunimatsu, Yutaka; Ogihara, Naomichi; Shimizu, Daisuke; Takano, Tomo; Tsujikawa, Hiroshi; Ishida, Hidemi
Abstract: The middle Miocene stem kenyapithecine Nacholapithecus kerioi (16–15 Ma; Nachola, Kenya) is represented by a large number of isolated fossil remains and one of the most complete skeletons in the hominoid fossil record (KNM-BG 35250). Multiple fieldwork seasons performed by Japanese–Kenyan teams during the last part of the 20th century resulted in the discovery of a large sample of Nacholapithecus fossils. Here, we describe the new femoral remains of Nacholapithecus . In well-preserved specimens, we evaluate sex differences and within-species variation using both qualitative and quantitative traits. We use these data to determine whether these specimens are morphologically similar to the species holotype KNM-BG 35250 (which shows some plastic deformation) and to compare Nacholapithecus with other Miocene hominoids and extant anthropoids to evaluate the distinctiveness of its femur. The new fossil evidence reaffirms previously reported descriptions of some distal femoral traits, namely the morphology of the patellar groove. However, results also show that relative femoral head size in Nacholapithecus is smaller, relative neck length is longer, and neck–shaft angle is lower than previously reported for KNM-BG 35250. These traits have a strong functional signal related to the hip joint kinematics, suggesting that the morphology of the proximal femur in Nacholapithecus might be functionally related to quadrupedal-like behaviors instead of more derived antipronograde locomotor modes. Results further demonstrate that other African Miocene apes (with the exception of Turkanapithecus kalakolensis ) generally fall within the Nacholapithecus range of variation, whose overall femoral shape resembles that of Ekembo spp. and Equatorius africanus . Our results accord with the previously inferred locomotor repertoire of Nacholapithecus, indicating a combination of generalized arboreal quadrupedalism combined with other antipronograde behaviors (e.g., vertical climbing).